Long-run expectations of households - Christoph Breunig; Iuliia Grabova; Peter Haan; Felix Weinhardt; Georg Weizsäcker (Journal of Behavioral and Experimental Finance, 2021)
The rational expectations assumption, e.g. in life-cycle models and portfolio-choice models, prescribes that all actions are in line with a well-structured and unbiased system of expectations. In reality, justification and identification of expectations are nontrivial, and we lack empirical evidence especially for the long run. This paper starts to fill this gap and elicits short-run and long-run expectations of a sample of households that is designed to be representative of the universe of German households. We focus on expectations about three highly welfare-relevant markets: the stock market, the labor market, and the housing market. We show that linear extrapolations of short-run expectations can approximate long-run expectations in the labor market, but not in financial or housing markets. In the latter two markets, long-run expectations of households are severely below linear price growth and far below historical values. This extreme pessimism does not extend to the labor market, where expectations are fairly close to historical values. We also document substantial heterogeneity of expectations by socio-economic and personal characteristics, e.g., females are more pessimistic than males about outcomes in all markets.
Keywords: D14; D18; D84; J31; 330; Long-run expectations; Biased beliefs; Returns to education